2017
DOI: 10.3390/ijms18040699
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Active Anthocyanin Degradation in the Petals of Rosa chinensis and Brunfelsia calycina Reveals the Effect of Gallated Catechins on Pigment Maintenance

Abstract: Anthocyanin degradation decreases ornamental or nutritional values of horticultural products. To investigate factors that may influence colour change in flower development, anthocyanin degradation was compared between the flowers of Brunfelsia calycina and Rosa chinensis, which show rapid and slow degradation, respectively. In-gel activity assays, high performance liquid chromatography (HPLC) analysis of tannins, enzyme kinetics measurement and immune-detection of anthocyanin degradation related-perioxidases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 51 publications
(76 reference statements)
0
24
0
Order By: Relevance
“…More anthocyanin accumulation in the CH+ 5 mM OA‐treated fruit could be due to the role of OA as an elicitor in anthocyanin biosynthesis (Sayyari et al., 2010). It has been proved previously that total anthocyanin decreases during due to increase in the activity of PPO and POD enzymes and accumulation of H 2 O 2 (Luo et al., 2017). Therefore, in the present study, observed decrease in the PPO activity (Figure 4a) and H 2 O 2 content (Figure 2c) via application of CH, organic acid, and their combination could be one of the main reasons for maintaining anthocyanin content.…”
Section: Resultsmentioning
confidence: 91%
“…More anthocyanin accumulation in the CH+ 5 mM OA‐treated fruit could be due to the role of OA as an elicitor in anthocyanin biosynthesis (Sayyari et al., 2010). It has been proved previously that total anthocyanin decreases during due to increase in the activity of PPO and POD enzymes and accumulation of H 2 O 2 (Luo et al., 2017). Therefore, in the present study, observed decrease in the PPO activity (Figure 4a) and H 2 O 2 content (Figure 2c) via application of CH, organic acid, and their combination could be one of the main reasons for maintaining anthocyanin content.…”
Section: Resultsmentioning
confidence: 91%
“…The dominant pigments in rose petals are carotenoids and anthocyanins, which provide yellow and pink colors, respectively. Typically, orange petals result as a mixture of anthocyanins and carotenoids [ 4 , 5 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Roses are an important floricultural crop and are the most popular cut flowers because of their various floral colors and shapes [ 3 ]. Flower color is the major horticultural characteristic of rose cultivars [ 3 , 4 ]. A broad range of floral colors are now available in the rose after many years of cultivar development, and many studies have investigated the contributions of rose pigments [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Color make flowers attractive and facilitates the reproduction of flowering plants. Besides that, colored flowers can also be used by humans to beautify their environment, in addition to the health benefits of pigments as dietary components, which provide protection against a wide range of human diseases [ 1 , 2 , 3 ]. As a critical index to judge the ornamental and/or economic value, understanding the molecular basis of flower color formation would improve the applicable occasions of flowers.…”
Section: Introductionmentioning
confidence: 99%